Nutrient enrichment intensifies hurricane impact in scrub mangrove ecosystems in the Indian River Lagoon, Florida, USA. Issue 11 (1st November 2015) - Feller, Ilka C.; Dangremond, Emily M.; Devlin, Donna J.; Lovelock, Catherine E.; Proffitt, C. Edward; Rodriguez, Wilfrid
Abstract : Mangroves are an ecological assemblage of trees and shrubs adapted to grow in intertidal environments along tropical, subtropical, and warm temperate coasts. Despite repeated demonstrations of their ecologic and economic value, multiple stressors including nutrient over‐enrichment threaten these and other coastal wetlands globally. These ecosystems will be further stressed if tropical storm intensity and frequency increase in response to global climate changes. These stressors will likely interact, but the outcome of that interaction is uncertain. Here, we examined potential interaction between nutrient over‐enrichment and the September 2004 hurricanes. Hurricanes Frances and Jeanne made landfall along Florida's Indian River Lagoon and caused extensive damage to a long‐term fertilization experiment in a mangrove forest, which previously revealed that productivity was nitrogen (N) limited across the forest and, in particular, that N enrichment dramatically increased growth rates and aboveground biomass of stunted Avicennia germinans trees in the interior scrub zone. During the hurricanes, these trees experienced significant defoliation with three to four times greater reduction in leaf area index (LAI) than control trees. Over the long term, the +N scrub trees took four years to recover compared to two years for controls. In the adjacent fringe and transition zones, LAI was reduced by >70%, but with no differences based on zone or fertilization treatment. Despite continued delayed mortality for at least five years after the storms, LAI in the fringe and transition returned to pre‐hurricane conditions in two years. Thus, nutrient over‐enrichment of the coastal zone will increase the productivity of scrub mangroves, which dominate much of the mangrove landscape in Florida and the Caribbean; however, that benefit is offset by a decrease in their resistance and resilience to hurricane damage that has the potential to destabilize the system.